Japan's Territory under International Law - Kanehara, Atsuko; Yanagihara, Masaharu (International Law E-Books Online, Collection 2025., 2024)
This volume sheds light on Japan's territorial situation from a unique perspective by analyzing the historical evolution of the concept of "territory" and the various legal theories on resolving territorial disputes. Each of the chapters in this